Caracterização de movimentos mandibulares na disfunção temporomandibular por meio de parâmetros cinemáticos - Bellomo Júnior, Douglas Peres (2015)
This study quantifies the mandibular movements of opening and close, laterotrusion and protrusion, obtained from 20 healthy subjects and 20 TMD subjects subdivided into 10 individuals with myopathy and 10 individuals with arthropaty, selected by Research Diagnostic Criteria (RDC) protocols. These movements of all subjects were captured and measured at maximum length, medium velocity and acceleration and deviation during your trajectories, were captured by three infrared cameras and measured by a computational system previously developed by the University Federal of Uberlândia, which, in this research was named Jaw Capture. This system receives images simultaneously from nine reflective markers and send and process this data to a computer using a firewire system through a mathematical approach to analyze and quantify in 3D (at X, Y and Z axis), the marker trajectories. The reflective markers were positioned by supporting systems fixed on vestibular face of lower incisives and skin surface of face. The movement ranges are similar among all individuals, meanwhile the deviation and the medium velocity and acceleration are very different between target and control group after statistical analysis. This system being proves reliable and efficient.